Term Limitations for State Power - Ahmad Rizani; Aziz Saputra; Juang Aulia Akbar; Zulfian Achmad Noviandi; Surya Sukti (INDO PUBLISHING, 2026)
This study examines the fundamental concepts of authority and legitimacy within the framework of introductory legal studies, along with their practical implications in the operation of modern states. Authority is understood as legally grounded power exercised by state institutions within clearly defined limits, while legitimacy refers to the societal acceptance that justifies such power. The discussion highlights that authority cannot function effectively without legitimacy, and legitimacy itself depends on the lawful and responsible exercise of authority. Furthermore, the paper explores the limitations imposed on state administrators, emphasizing principles such as legality, the rule of law, separation of powers, human rights protection, accountability, and ethical considerations as essential safeguards against the abuse of power. In addition, it analyzes various sources of legitimacy, including legal procedures, public consent, cultural traditions, governmental performance, moral integrity, and international recognition. The study also underscores the importance of term limits as a mechanism to prevent the concentration of power, encourage leadership renewal, and strengthen accountability within governance systems. Overall, the findings demonstrate that a stable and just legal system requires a balanced relationship between authority, legitimacy, and institutional constraints, ensuring that power is exercised responsibly and in accordance with the public interest.